PENGELOLAAN SAMPAH PLASTIK DENGAN METODE ECOBRICK SEBAGAI UPAYA MENDUKUNG SDGS KE-12: KONSUMSI DAN PRODUKSI YANG BERTANGGUNG JAWAB - Rahmatullah, Sri; Verawati, Ni Nyoman Sri Putu (Jurnal Wicara, 2024)
Ecobricks can be one way to overcome environmental pollution problems by reducing plastic waste and utilizing it into useful furniture. Through the KKN PMD (Village Community Empowerment) community service activity held by Mataram University Students with the aim of inviting elementary school students to utilize and process waste into new useful products. This activity was carried out on July 8, 2024 at 09.00-12.00 WITA which was held at SDN SUBAHNALA, Peresak Village, Batukliang District, Central Lombok. The method we apply in this community service is the delivery of material verbally and a demonstration of making ecobricks. It is hoped that this activity can educate students so as to increase participation in managing sustainable waste. The implementation of this activity received a positive response from enthusiastic students who have the potential to reduce the amount of waste produced from student consumption activities. The results of this KKN community service activity are to increase student awareness of the importance of maintaining environmental cleanliness, how to manage plastic waste, so that students have broader knowledge about environmental conservation efforts through the use of ecobricks in construction. Ecobricks that can be used as furniture for various purposes, such as tables and chairs.